The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1097/01.opx.0000177804.53192.15
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Repeatability of Anterior Chamber Depth Measurements With Pentacam and Orbscan

Abstract: In the assessment of normal eyes, the differences of ACD values measured with Orbscan and Pentacam were within clinically acceptable levels, and inter- and intraobserver variability was considerably below clinically significant levels. Thus, these two modalities can be regarded as interchangeable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 17 publications
3
103
2
2
Order By: Relevance
“…For individual groups ACA mean was 39. 20 The efficacy of the Pentacam parameters to screen out the open-angle (SC Grade 3 and 4) and narrow-angle (SC Grade 1 and 2) eyes as defined above were studied using ROC curves. According to the partition analysis, when ACA was used as the reference to classify the open-angle and narrow-angle eyes value of 20 o using the Pentacam, results in 52.6% sensitivity and 100% specificity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For individual groups ACA mean was 39. 20 The efficacy of the Pentacam parameters to screen out the open-angle (SC Grade 3 and 4) and narrow-angle (SC Grade 1 and 2) eyes as defined above were studied using ROC curves. According to the partition analysis, when ACA was used as the reference to classify the open-angle and narrow-angle eyes value of 20 o using the Pentacam, results in 52.6% sensitivity and 100% specificity.…”
Section: Resultsmentioning
confidence: 99%
“…As with all optical and acoustic techniques, correction of the image distances needs to be made for the refractive index and the curvature of intervening surfaces (20)(21) . The digital Scheimpflug photograph, therefore, decreases in size perpendicular to the direction of the optical axis, reducing the curvature radius and increasing depths and thicknesses along this axis compared with the original photograph.…”
mentioning
confidence: 99%
“…Of special concern was to show how Pentacam measurements taken from normal corneas compared to those from the more commonly clinically used autokeratometric method. Although numerous studies [6][7][8][9][10][11][12] have been performed to compare different pachymetry methods, to our knowledge this is the first study evaluating the keratometry measurements of the Pentacam in normal eyes. Currently, articles about pachymetry and central corneal thickness measurements between the Pentacam and other approaches have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Initial publications [6][7][8][9][10][11][12] have reported excellent repeatability with measurements of central corneal thickness and anterior chamber depth measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The Pentacam HR (Oculus, Wetzlar, Germany) and the Galilei G4 (Ziemer, Switzerland) are two clinical tomographers that are both based on Scheimpflug cameras. Beside corneal parameters, these devices also have the ability to measure the ACD, ACA, PD, and ACA, and they (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) or WTW distance (20)(21)(22) . However, to our knowledge, a side by side comparative study has not previously been reported.…”
Section: Introductionmentioning
confidence: 99%